Dose Adjustment Model of Paliperidone in Patients With Acute Schizophrenia: A post hoc Analysis of an Open-Label, Single-Arm Multicenter Study - Si, Tianmei; Sun, Ling; Zhang, Yilong; Zhang, Lili (Frontiers in Psychiatry, 2021)
This study aimed to investigate the factors that influenced the clinicians to adjust the paliperidone dose in the acute phase of schizophrenia. This was a post hoc study of an 8-week, open-label, single-arm multicenter trial which evaluated the efficacy, safety, and tolerability of flexible doses of paliperidone ER (3-12 mg/day) in patients with acutely exacerbated schizophrenia. Patients were divided into groups according to the dose at week 8 (3, 6, and 9-12 mg). The responder was defined as the reduction percentage in the Positive and Negative Syndrome Scale (PANSS) total score of ≥30%. According to the chi‐squared automatic interaction detection algorithm, decision tree models predicting an increase in the dose of paliperidone ER were established. The multivariable logistic regression analysis showed that lower age at onset, higher baseline PANSS positive subscale score, and lower baseline Personal and Social Performance Scale (PSP) score were significant predictors of increased dose in responders. A decision tree based on 4-week Marder positive factor, Clinical Global Impression (CGI), and BMI was successfully developed to guide the dose adjustments of paliperidone ER in the acute phase of schizophrenia. Patients with young-onset age, severe baseline symptoms, and poor function are more likely to benefit from high dosage.